PS 14-61 CLONIDINE AND OUTCOME IN PATIENTS HOSPITALIZED WITH GRADE III HYPERTENSION: A REPORT FROM A RURAL HOSPITAL IN WEST BORNEO. (September 2016) - Sudharsono, Albert; Soenarto, Budi; Effendi, Bonita; Hanafy, Dicky
Abstract : Objective: Hypertension has become one of the health problems in the world. Based on Indonesia Basic Health Research 2013, the prevalence of hypertension is 25.8%. One of the anti-hypertension drugs is clonidine, an alpha-blocker. Although clonidine is not an option as first line therapy by the guidelines, this drug still plays some role in the management of hypertension, especially due to its availability, efficacy and low price in rural area. We evaluate clonidine compared with other anti-hypertension drugs to treat. Design and Method: Within October 2014 - December 2015, a case-control study was conducted among hospitalized patients with moderate to severe hypertension. Case group was patients treated by clonidine and combining it with two anti hypertension drugs (n = 45). Control group was random patients treated with at least two anti hypertension drugs (n = 90). The drug-combinations were described as Angiotensin Converting Enzyme Inhibitor (ACEi), Calcium Channel Blocker (CCB), Beta Blocker (BB) and Diuretics. Results: A total of 135 hospitalized patients were conducted in this study, 78 patients (57.8%) were female. All subjects were admitted with hypertension grade 3 according to the 2013 ESC/ESH guideline. Mostly reported comorbid include Stroke (29.6%), Diabetes type II (20.4%), and Chronic Kidney disease (16.1%). In mmHg, median systolic BP was 210 (160–300) and diastolic BP was 120 (100–190). There is significant difference of proportion between outcome and clonidine +/- other drugs (p = 0.007). Further analysis showed that the probability of mortality in patients treated without clonidine was 23%, compared to those with clonidine (OR 0.32, p = 0.03 95% CI 0.11–0.94). Conclusions: The reference control group had less risk of mortality than patients treated with clonidine. The administration of clonidine needs to be further evaluated especially as first line therapy in the management of grade III hypertension.